2021
DOI: 10.1111/fcp.12663
|View full text |Cite
|
Sign up to set email alerts
|

Short‐chain fatty acids increase intracellular calcium levels and enhance gut hormone release from STC‐1 cells via transient receptor potential Ankyrin1

Abstract: Short‐chain fatty acids (SCFAs), metabolites of colonic bacterial fermentation of complex carbohydrates, are closely related to the release of gut hormones. In this study, we examined the involvement of transient receptor potential ankyrin 1 (TRPA1) in SCFA‐induced increase in intracellular calcium ([Ca2+]i) and its impact on gut hormone secretion using naturally TRPA1 expressing intestinal secretin tumour cell‐1 (STC‐1) cell line. Individual SCFAs and their physiological mix enhanced calcium influx in TRPA1‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 61 publications
2
4
0
Order By: Relevance
“…Some bacterial strains (Lactobacillus, Bacteroides, Fecalibacterium, Anaerostipes butyraticus) modulate the goblet cell differentiation and stimulate mucus production. , Their persistently low abundances, in HFD and HFD + CPZ and HFD + CPZ + IMO groups, might also be impeding the improvement in mucus production. On the other hand, the positive influence of prebiotics on gut microbiota , supports our observation of increase in abundance of commensal bacteria in the HFD + IMO group. The increase in mucin-producing bacteria such as Lactobacillus, Anaerostipes butyraticus, and Bacteroides, as well as bacteria that degrade mucus, such as Akkermansia muciniphila and Bacteroides ,,, in the HFD + IMO group suggests a positive effect of IMO in preventing HFD-induced complications.…”
Section: Discussionsupporting
confidence: 84%
“…Some bacterial strains (Lactobacillus, Bacteroides, Fecalibacterium, Anaerostipes butyraticus) modulate the goblet cell differentiation and stimulate mucus production. , Their persistently low abundances, in HFD and HFD + CPZ and HFD + CPZ + IMO groups, might also be impeding the improvement in mucus production. On the other hand, the positive influence of prebiotics on gut microbiota , supports our observation of increase in abundance of commensal bacteria in the HFD + IMO group. The increase in mucin-producing bacteria such as Lactobacillus, Anaerostipes butyraticus, and Bacteroides, as well as bacteria that degrade mucus, such as Akkermansia muciniphila and Bacteroides ,,, in the HFD + IMO group suggests a positive effect of IMO in preventing HFD-induced complications.…”
Section: Discussionsupporting
confidence: 84%
“…[ 28 ] Another study reported that short‐chain fatty acids, which are organic acids, increase intracellular Ca 2+ levels and enhance GLP‐1 release from STC‐1 cells via transient receptor potential Ankyrin 1. [ 29 ] In the present study, the combined with GABA and MA synergistically increased [Ca 2+ ] i . Because intracellular Ca 2+ acts as a key second messenger in the release of peptide hormones, we reasoned that MA‐dependent changes in [Ca 2+ ] i may play a synergistic role in GLP‐1 secretion with GABA.…”
Section: Discussionsupporting
confidence: 57%
“…Short-chain fatty acids (SCFAs), the enterosyne released from anaerobic bacterial fermentation of dietary substrates (mainly prebiotic containing indigestible carbohydrates) [ 19 , 20 , 21 ], possess gut modulatory properties. They are significantly involved in the maintenance of colonic mucus production, intestinal barrier integrity, and also have anti-inflammatory and immunomodulatory properties [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%